2021
DOI: 10.35906/jm001.v7i1.718
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employee Benefit Liabilities, Sales Growth, Capital Intensity, and Earning Management on Tax Avoidance

Abstract: Tax avoidance is a strategy that is common in tax management. As part of management strategy, tax avoidance is important to know for a manager. The purpose of this research is to examine the level of tax avoidance of the manufacturing industry in Indonesia and the role of employee benefit liabilities, sales growth, capital intensity, and earnings management in effecting this. This study uses purposive sampling and 78 manufacturing companies listed on Indonesia Stock Exchange (IDX) from 2016 to 2019 that were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
1
6
1
3
Order By: Relevance
“…If sales growth or sales growth increases, it shows that there is an increase in the company's operating capacity(Budiman & Setiyono in (Oktamawati, 2017). Meanwhile, in the research of Marfiana & Putra (2021); Mahanani et al (2017) revealed a different thing, namely that there was no influence between sales growth on tax avoidance. Therefore, in this study to test the following hypotheses:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If sales growth or sales growth increases, it shows that there is an increase in the company's operating capacity(Budiman & Setiyono in (Oktamawati, 2017). Meanwhile, in the research of Marfiana & Putra (2021); Mahanani et al (2017) revealed a different thing, namely that there was no influence between sales growth on tax avoidance. Therefore, in this study to test the following hypotheses:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous research on sales growth in tax avoidance found inconsistencies in the results obtained. Research conducted by Marfiana & Putra (2021), states that the higher the company's sales growth, the higher the practice of tax avoidance. This research is in line with research by Nugraha & Mulyani (2019); Hamilah & Situmorang (2021); Faradisty et al (2019) states that sales growth has an effect on tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Net cash from operating activities terhadap tax avoidance oleh Susilowati et al (2020), dan Marfiana & Putra (2021) menemukan hasil significant negatif. Kemudian penelitian dari Wardani & Nugrahanto (2022) menemukan hasil significant positif.…”
Section: Hubungan Antar Variabel: Corporate Social Responsibility Ter...unclassified
“…Hal inilah membuat adanya keinginan untuk meminimalkan beban pajak yang dibayarkan sehingga kompensasi atas kinerja yang didapat manajemen perusahaan tidak mengurangi pertumbuhan laba perusahaan. Hasil ini didukung oleh Marfiana & Putra (2021) Hasil pengujian goodness of fit model menunjukkan Adjusted R-squared untuk variabel dependen menggunakan proxy current ETR adalah 0,070344. Hal ini menunjukkan bahwa variabel independen pada penelitian hanya dapat mengungkapkan 7,03% dari variabel dependen, dengan sisanya 92,97% diungkapkan oleh variabel yang tidak ada dalam penelitian ini.…”
Section: Hasil Uji Tunclassified
“…According to (Hidayati et, al., 2021), fixed assets in a company can reduce the tax burden that must be paid due to a depreciation of fixed assets. Based on previous research by (Anindyka et, al., 2018;Aryatama & Raharja, 2021;Darsani & Sukartha, 2021;Dharma & Noviari, 2017;Dwiyanti & Jati, 2019;Marfiana et,al., 2021;Noor & Sari, 2021) proves the intensity variable capital positively affects the tax avoidance variable. This problem is in accordance with agency theory.…”
Section: Effect Of Capital Intensity On Tax Avoidancementioning
confidence: 99%